Application of CNN-ATTBiLSTM Hybrid Algorithm in Natural Language Processing - Xiang, Yang; Song, Hong (Journal of Vibration Testing and System Dynamics, 2026)
Aiming at the problems that traditional machine learning algorithms such as SVM rely too much on emotional dictionary, grammatical mechanism and low recognition rate in processing text sentiment by natural language, a different ratio CNN-ATTBiLSTM algorithm based on the algorithm is proposed in this paper. First, the CNN algorithm is used to process the local features, and the CNN feature fusion method is used to integrate ATTBiLSTM (two-way long-term and short-term memory network based on attention mechanism) at the output, Then the two algorithms are combined in different ratios to find the highest F1 value as the combination ratio. Finally, the algorithm proposed in this paper is compared with the traditional machine learning algorithms and the proposed algorithms in the experimental data set. The results show that the new algorithm is 0.85% better than the equal weight ratio CNN-ATTBiLSTM algorithm. So it is the best algorithm compared with other algorithms.